Adoption of Social Media by Small- and Medium-Sized Healthcare Enterprises - Silvia Zilber; Sonia Monken; Filipe Quevedo-Silva (BBR: Brazilian Business Review)
Social media such as YouTube, Facebook, and Twitter can affect the way healthcare providers deliver their services. As low-cost tools, their use by small- and medium-sized enterprises (SMEs) in the healthcare sector could deliver competitive advantages. Several studies have shown that these tools are still underutilized by companies in this segment. Thus, the objective of the present study was to investigate which factors lead to the adoption of social media by SMEs in the healthcare sector in Brazil. To this end, a model for the adoption of organizational innovation was used in a causal study. A survey was conducted with 211 healthcare SMEs. The data analysis method was structural equation modeling (SEM), and SmartPLS 2.0 M3 software was used for the analyses. The results showed that both the perceived characteristics of the social media and the characteristics of the adopter are factors that contribute to the adoption of these media by the enterprises. Environmental influences were shown to not be relevant for the adoption of the media by the enterprises in the sample.